2008
DOI: 10.1002/ijc.23934
|View full text |Cite
|
Sign up to set email alerts
|

NO‐sulindac inhibits the hypoxia response of PC‐3 prostate cancer cells via the Akt signalling pathway

Abstract: Nitric oxide-donating non-steroidal anti-inflammatory drugs are safer than traditional NSAIDs and inhibit the growth of prostate cancer cells with greater potency than NSAIDs. In vivo, prostate cancer deposits are found in a hypoxic environment which induces resistance to chemotherapy. The aim of this study was to assess the effects and mechanism of action of a NO-NSAID called NOsulindac on the PC-3 prostate cancer cell line under hypoxic conditions. NO-sulindac was found to have pro-apoptotic, cytotoxic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…This work complements and expands our previous studies which demonstrated the cytotoxic effects of NO-NSAIDs on prostate cancer cells under normoxia and hypoxia [6,7]. The use of both 2D and 3D models showed that NO-sulindac radiosensitised the PC-3 hormone insensitive prostate cancer cell line, not only under normoxia but particularly under chronic hypoxia.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This work complements and expands our previous studies which demonstrated the cytotoxic effects of NO-NSAIDs on prostate cancer cells under normoxia and hypoxia [6,7]. The use of both 2D and 3D models showed that NO-sulindac radiosensitised the PC-3 hormone insensitive prostate cancer cell line, not only under normoxia but particularly under chronic hypoxia.…”
Section: Discussionsupporting
confidence: 79%
“…4A). As we have shown previously, treatment of PC-3 cells with 25μM NO-sulindac under both normoxia and hypoxia reduces the levels of HIF-1α [7]. Furthermore, HIF-1α levels were undetectable on western blotting following NO-sulindac and radiation treatment at 8, 24 or 48 hours post-irradiation (Fig.…”
supporting
confidence: 73%
See 3 more Smart Citations